FENOMENA TEKANAN OSMOSIS LARUTAN SUKROSA SEBAGAI DASAR PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF - Ami Ferdina, - (2019)
The research entitled "Phenomenon of Osmosis Pressure as a Basis for Development an Interactive Multimedia Learning" aimed to represent the phenomenon of osmotic pressure using an simple apparatus design that produces the experimental data as a reference in developing an interactive multimedia. The research design used is Developmental Research. The instruments used in data collection in this research were the interview sheets and the apparatus and the procedures. An apparatus and experiment procedures have been test for sucrose solution. The results of this research indicate that the apparatus can display the osmotic pressure phenomenon of sucrose solution which is characterized by an increase the height of solution in the apparatus. The concentration of sucrose solution is 0,035 M; 0,05 M; 0,055 M; and 0,1 M. Relationship between concentration of sugar solution with the magnitude of the osmotic pressure is the higher the concentration of sucrose solution (concentrated solution), the higher the deviation produced between the experimental data and the theoretical calculation data. The time required to conduct an osmotic pressure of sucrose solution is three days. Based on the experiments using an apparatus that have been designed, the resulting data is difference with theoretical calculation data. However, the experimental data of osmotic pressure is produced by sucrose solution can be used as a basis for the development of interactive multimedia learning that presents an animation of osmotic pressure phenomenon